2014
DOI: 10.1177/0961203313519157
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous changes in serum HMGB1 and IFN-α levels and in LAIR-1 expression on plasmatoid dendritic cells of patients with juvenile SLE.. New therapeutic options?

Abstract: We investigated the simultaneous changes in serum levels of HMGB1 and IFN-α as well as in LAIR-1 expression on plasmatoid dendritic cells (pDCs) of juvenile systemic lupus erythematosus (jSLE) patients in order to explore their involvement in the disease pathogenesis and their correlation with disease activity and other characteristics. In total, 62 blood samples were studied from 26 jSLE patients (18 girls), aged 8-16 years. Twenty healthy subjects (16 girls) of comparable age were included as healthy control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 29 publications
(68 reference statements)
3
25
1
3
Order By: Relevance
“…Aside from reduced expression of CD33 and LAIR-1, C1q-mediated LAIR-1/CD33 inhibitory activity may be compromised by auto-antibodies directed either to gC1q and/or CLR, both of which have been described in SLE 4648 . Because LAIR-1 is also abnormally distributed on B cells and plasmacytoid DCs in SLE 4951 , abnormal C1q function in SLE may be linked to impaired LAIR-1 expression on these cell lineages, independent of CD33.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from reduced expression of CD33 and LAIR-1, C1q-mediated LAIR-1/CD33 inhibitory activity may be compromised by auto-antibodies directed either to gC1q and/or CLR, both of which have been described in SLE 4648 . Because LAIR-1 is also abnormally distributed on B cells and plasmacytoid DCs in SLE 4951 , abnormal C1q function in SLE may be linked to impaired LAIR-1 expression on these cell lineages, independent of CD33.…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, the single genetic ablation of SCARF1 was shown to lead to impaired apoptotic cell uptake and accumulation, immune cell activation, and a lupus-like disorder in mice, characterized by antinuclear autoantibodies and nephritis[62*]. LAIR-1 is expressed on both myeloid and lymphoid cells, but a reduction in expression on SLE B cells [64] and pDCs [65] has been reported. C1q binding to LAIR-1 delivers an ITIM-mediated inhibitory signal, resulting in the blockade of dendritic cell differentiation from monocytes, and inhibition of IFNa production by pDC [63*].…”
Section: Accumulation Modification and Downstream Consequences Of Dementioning
confidence: 99%
“…As mentioned before, ELISA is not suitable for measuring HMGB1 in active SLE patients, but from these data, it is suggested that active SLE patients will have much higher amounts of HMGB1 in their serum. Recently increased HMGB1 levels were reported in juvenile SLE patients (70).…”
Section: Hmgb1 In Sle Patients and Other Rheumatic Diseasesmentioning
confidence: 98%